Flora of the projected Mzhasnkyi National Nature Park (Kharkiv Region). Part 1: Pinewood complex - Bondarenko, H.M. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2025)
In the territory of the Kharkiv Region, pine forests are understudied, and only small areas of pine forests are protected. At the same time, there are risks for the pine forests and their biodiversity associated with a high level of economic activity, recreational load, and over the past 3 years, with active combat activity. This encourages research and preservation of the most valuable areas of pine forests in the territory of the Kharkiv Region. To protect the valley complexes of the Mozh River, including pine forests, a project for organizing the Mzhansky National Nature Park was proposed. From 2023 to 2024, the flora of the designated park was studied using the route reconnaissance method. It was established that the flora of the studied territory consists of 529 species, subspecies and hybrids of vascular plants. The phytobiota is represented by 81 families, among which the leading ones are Asteraceae, Poaceae, Cyperaceae, Fabaceae, Rosaceae, Caryophyllaceae, Lamiaceae, Brassicaceae, Plantaginaceae s.l., Apiaceae, Boraginaceae, and Ranunculaceae. The analysis of the flora by the main edaphic factors showed that the hygromorphes spectrum is dominated by groups of hygromesophytes (24.3%), mesophytes (23.4%), and submesophytes (23.0%). Compared with other studied forests in the Kharkiv Region, the studied territory is characterized by more humid and diverse conditions. In terms of nitrate content, general salt regime and substrate acidity, the studied territory has typical conditions for forests in the Kharkiv region. According to the results of the analysis of the flora synanthropization, it was established that the degree of transformation is 51.1%, which is less than similar indicators of other local floras in the Kharkiv Region. Transformation occurs mainly due to apophytes (31.1%). At least 106 alien plant species occurred, more than half of which are of Mediterranean or North American origin. Among them are new species to the Kharkiv Region: Commelina communis, Bidens connata, and Sedum album. During the research, 40 protected plant species were revealed. Among them, 30 are protected at the regional level (Bistorta officinalis, Comarum palustre, Dryopteris carthusiana, Paris quadrifolia, Pyrola rotundifolia, Thelypteris palustris, etc.), 10 are included in the Red Book of Ukraine (Botrychium lunaria, Epipactis helleborine, Neottia ovata, Pulsatilla pratensis, Stipa borysthenica, etc.) and 3 species are included in Resolution 6 of the Bern Convention (Jurinea cyanoides, Pulsatilla patens, and Salvinia natans). Several rare species in the region that do not have a protected status were also identified (Carex remota, Luzula pilosa, Peucedanum palustre, etc.). A significant proportion of rare and protected species are at the southern limit of their distribution, therefore they are particularly vulnerable in the study area.